PERANCANGAN TEKSTIL PAKAIAN DENGAN PEWARNA DARI SAMPAH MANGROVE DAN PENERAPAN MOTIFNYA DENGAN PADUAN TEKNIK IKAT CELUP DAN ECO PRINTING - Dewi Diana Safitri; Tiwi Bina Affanti (Ornamen, 2022)
The background of this design, there is an exploration of manual textile techniques among textile designers, this is in line with the demands of the times, namely, the development of existing trends in order to meet the needs of consumers and the market. The combination of tie-dying and eco-printing techniques attracts attention to be explored again using natural dyes with the addition of embroidery techniques on Bemberg cloth media, which will produce textiles with novelty in their aesthetic motifs. The purpose of this design is to produce clothing textiles with novelty in their unique motif aesthetics among textile designers to meet the needs of consumers and the market. The novelty value offered in this design is the design of clothing textiles according to fashion patterns with a combination of dyeing and eco printing techniques with embroidery techniques. Natural coloring using extraction from mangrove waste. Composing motifs using natural dyes from mangrove waste with two fixations of quicklime and tunjung to obtain varied visual aesthetics in one natural coloring. The media used in this blend of tie-dying and eco-printing techniques is bemberg cloth. Bemberg cloth material was chosen because it has very good absorption. The design method uses the SP Gustami theory. This design produces 6 unique designs with visual ideas of line, plane and color, which can be achieved by a combination of tritik, jumputan tie-dyed and eco printing techniques, three of which are applied to sheets of cloth measuring 200cm long and 120cm wide. It is hoped that the "Design of Clothing Textiles with Dye from Mangrove Waste and the Application of its Motifs with a Combination of Ikat Dip and Eco Printing Techniques" can add variety to fashion products that have unique, distinctive and limited edition characters.